Tetraphenylglycolide tetrahydrofuran monosolvate - Lubabalo Ndima; Eric Cyriel Hosten; Richard Betz (IUCrData)
The title compound, C28H20O4·C4H4O, is the cyclic ester anhydride of benzilic acid. A disordered solvent molecule is present in the structure. The asymmetric unit contains half the acid-derived molecule. C—H...O contacts connect the constituents of the title compound into a three-dimensional network.